Analisa Faktor Eksternal pada Perencanaan Aplikasi Jasa Titip Barang - Diki Ihwan Mulhaedi; Tantri Yanuar Rahmat Syah; Dimas Angga Negoro; Suwarto Suwarto (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze external factors that influence the planning of a personal shopping service application, a service that is increasingly in demand in today's digital era. External factors such as market conditions, industry competition, government regulations, and technological developments are important variables that need to be considered in the development of this application in order to meet consumer needs and compete effectively. The research method uses a qualitative descriptive approach with data collection through literature studies, expert interviews, and market observations. Data analysis was carried out thematically with a focus on identifying and evaluating the influence of these external factors on application development planning. The results of the analysis show that changes in local and global regulations, trends in digital consumer behavior, and advances in communication technology have a significant impact on the planning strategy of personal shopping service applications. This study provides practical recommendations for application developers to anticipate external dynamics and increase the competitiveness of their products in the market. In terms of external strategy, the PEST (Political, Economic, Social and Technology) analysis shows that technological developments and the growth of e-commerce in Indonesia provide great opportunities for Titip.in to grow.